A comparative analysis of the anthropometric method and bioelectrical impedance analysis on changes in body composition of female volleyball players during the 2010/2011 season - Busko, K.; Lipinska, M. (Human Movement, 2012)
The aim of this study was to observe the changes in body composition by using two measurement methods - anthropometric analysis and bioelectrical impedance analysis (BIA) - on a group female volleyball players and to compare the results of both methods. Methods. Eleven female volleyball players participated in this study during the 2010/2011 season. Measurements of body composition were performed with an electronic body composition analyzer (BIA method) adjusted for STANDARD physical activity levels and then using the anthropometric method as per Piechaczek's formula. Total lean body mass (LBM), total body fat content (FAT) and body water content were measured. Measurements were taken before preseason training (Measurement 0), one week before the end of preseason training (Measurement 1), after the first (Measurement 2) and the second (Measurement 3) half of the competitive season and four weeks after the seasons' playoffs during the offseason (Measurement 4). Additionally, during Measurement 4, body composition measured by the BIA method was adjusted for ATHLETIC physical activity levels. Results. Body mass, lean body mass and body water content did not change throughout the analyzed period. Body fat mass, as determined by BIASTANDARD, increased from 20.7 ± 5.3 kg (Measurement 0) to 22.2 ± 5.0 kg (Measurement 1) but subsequently decreased to 21.2 ± 5.7 kg (Measurement 2) and remained at this level until the end of the competitive season. In the case of body fat as measured by the anthropometric method, a significant increase in fat was observed from 18.4 ± 3.0 kg to 19.3 ± 3.4 kg and then from 19.5 ± 3.5 kg to 19.8 ± 3.6 kg. Analysis of LBM and FAT values found significant differences between the values obtained using the BIA method at the ATHLETIC physical activity level and the results registered at the STANDARD level and those recorded by use of the anthropometric method. Conclusions. The results obtained using the BIA method set at the STANDARD mode of physical activity and those by the anthropometric method did not significantly differ. Significant correlation between the values obtained by the BIA method and anthropometric method was found.